Effect of Aerobic Exercise at Different Intensities on Intraocular Pressure in Young Males. Issue 11 (17th November 2022) - Alfaqeeh, Fatima; Djemai, Haidar; Hammad, Rami; Hammad, Saleh; Noirez, Philippe; Dabayebeh, Ibrahim M.
Abstract : Précis: High intensity aerobic exercise significantly reduced intraocular pressure in healthy young male adults. Objective: This study sought to determine how aerobic exercise at various intensities affects intraocular pressure (IOP) in young adults. Design: A repeated measures design was adopted. Participants: A group of 20 volunteers (mean age: 21.24±1.73 y) took part in this study. Methods: IOP was measured with a tonometer (iCare TA01i, Icare Finland, Finland). Subjects completed 4 cycle ergometer sessions. During the first session, power was increased by 60 W every 3 minutes until exhaustion, corresponding to peak power. For the 3 following tests, each lasting 25 minutes, subjects exercised at intensities of 50%, 70%, and 85% of peak power, respectively, and measurements were taken every 5 minutes. Main Outcome Measures: IOP, as determined using a tonometer, was the primary measure. Results: There was a significant reduction ( P <0.05) in IOP of both eyes during the 25 minutes high-intensity (85%) exercise test. There were also significant interactions between exercise durations and intensities. During high-intensity exercise, IOP, blood pressure, blood lactate, and the rating of perceived exertion were significantly related ( P <0.01). Conclusions: These data show a significant reduction in IOP at high-intensity aerobic exercise, which may have implications for the management of ocular health.